Are the take-off and landing phase dynamics of the volleyball spike jump related to patellar tendinopathy? - Bisseling, R. W.; Hof, A. L.; Bredeweg, S. W.; Zwerver, J.; Mulder, T. (British Journal of Sports Medicine, 2008)
Objective: The causal mechanism of the chronic sports injury patellar tendinopathy is not well understood. The aim of the present study was to compare ankle and knee joint dynamics during the performance of the volleyball spike jump between healthy volleyball players (n = 8) and asymptomatic volleyball players with previous patellar tendinopathy (n = 7).